Tax Cuts Starve the Beast! Evidence from Germany - Clemens Fuest; Florian Neumeier; Daniel Stöhlker (Center for Economic Studies and ifo Institute (CESifo), 2019)
The 'starving the beast' hypothesis claims that tax cuts lead to lower public spending, rather than higher debt levels and higher taxes in the future. This paper uses the institutional setting of German fiscal federalism to its advantage in order to explore how fiscal policy reacts to exogenous tax revenue shocks. We use panel data from the German states covering the period from 1992 to 2011, and assess to what extent exogenous changes in tax revenues affect aggregate public expenditure as well as specific sub-categories of government spending. Applying the narrative approach pioneered by Romer and Romer (2009), we construct a measure of exogenous tax shocks. This allows us to identify the causal effect of tax changes on fiscal policy. Our results suggest that an exogenous decrease in tax revenues triggers a reduction in public spending of roughly the same amount, with a delay of two to three years. We find that a revenue decline of one Euro reduces public spending on administration and, with a larger delay, social security, by 30 to 45 cents in each case. Spending on infrastructure declines by ten cents. We find no significant effects on spending on education, legal protection and public safety, or culture.
Keywords: E62; H11; H20; H62; H72; 330; taxation; fiscal policy; tax-spend; public expenditure; narrative approach